The up-regulation of SPTAN1 expression in Pancreatic adenocarcinoma is associated with tumor immune invasion and poor clinical prognosis - Wei Guo; LingYu Hu; ZhaoFeng Gao; XiaoRong Liu; XiaoDan Yang; XiaoGuang Wang (BMC Gastroenterology)
Abstract Background Pancreatic adenocarcinoma (PAAD) is a common malignancy with a very low survival rate. More and more studies have shown that SPTAN1 may be involved in the development and progression of a variety of tumors, including rectal cancer, Pancreatic adenocarcinoma, etc., and may affect their prognosis. Methods Bioinformatics technology was used to analyze the relationship between SPTAN1 expression in PAAD and immune cell infiltration, immune regulatory factors and chemokines, and cell experiments were used to verify the relationship between SPTAN1 knock down and migration, invasion, apoptosis and cycle changes of PAAD cell lines. In addition, immunohistochemical staining of SPTAN1 was performed by tissue microarray (TMA) to study the relationship between high expression of SPTAN1 and clinicopathological features and overall survival rate. Results The expression of SPTAN1 is significantly correlated with immune cell infiltration, immunomodulators, chemokines and their receptors. In addition, it was found that the knock-down of SPTAN1 inhibited the migration and invasion ability of PAAD cell lines, promoted the apoptosis of cell lines, and also affected the changes of cell cycle. Immunohistochemical staining using tissue microarray (TMA) showed that the high expression of SPTAN1 was associated with M stage (P = 0.004) and CA199 (P = 0.012), and the overall survival rate of the high expression group was significantly lower than that of the low expression group (P = 0.043). Conclusion Our results suggest that up-regulation of SPTAN1 is related to cell migration, invasion, apoptosis and cycle changes, and is associated with tumor immune invasion and poor prognosis of PAAD.